Two Sensory Channels Mediate Perception of Fingertip Force. (October 2014) - Brothers, Trevor; Hollins, Mark
In two experiments we examined the ability of humans to exert forces accurately with the fingertips, and to perceive those forces. In experiment 1 participants used visual feedback to apply a range of fingertip forces with the distal pad of the thumb. Participants made magnitude discriminations regarding these forces, and their just noticeable differences were calculated at a series of standards by means of a two-interval, forced-choice tracking paradigm. As the standard increased, participants demonstrated a relative improvement in force discrimination; and the presence of a possible inflection point, at approximately 400 g, suggested that two sensory channels may contribute to performance. If this is the case, the operative channel at low forces is almost certainly the slowly adapting type I (SA-I) channel, while another mechanoreceptor class, the SA-II nail unit, is a plausible mediator of the more accurate performance seen at high force levels. To test this two-channel hypothesis in experiment 2, we hydrated participants' thumbnails in order to reduce nail rigidity and thus prevent stimulation of underlying SA-II mechanoreceptors. This technique was found to reduce sensory accuracy in a force-matching task at high forces (1000 g) while leaving low force matching (100 g) unimpaired. Taken together, these results suggest that two sensory channels mediate the perception of fingertip forces in humans: One channel predominating at low forces (below approximately 400 g) and another responsible for perceiving high forces which is likely mediated by the SA-II nail unit.